DOI: 10.3990/1.9789036548823
|View full text |Cite
|
Sign up to set email alerts
|

Human intervention in rivers

Abstract: Samenvatting 16 met metingen. We simuleren over een periode van twintig jaar (1995-2015) de waterstanden in de Waal. Deze modelvoorspellingen laten een duidelijk waterstandsverlagend effect van Ruimte voor de Rivier zien. Een dertigjarige dataset van waterstands-en afvoermetingen is gebruikt om langjarige trends in metingen te analyseren. Uit deze metingen blijkt een gestage daling in de waterstand van tussen de 1 cm en 2 cm per jaar, wat wordt toegeschreven aan autonome bodemdaling. Een duidelijk waterstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 182 publications
(351 reference statements)
0
2
0
Order By: Relevance
“…The results of parameter identification and uncertainty estimation are usually presented in the form of confidence intervals for model outputs and parameter marginal distributions. The problem was defined on the basis of Bayes estimation using the generalized likelihood uncertainty estimation (GLUE) approach (Beven and Binley, 1992;Romanowicz and Beven, 2006). Parameter distributions are obtained using the Bayes formula:…”
Section: Parameter Identification and Uncertainty Analysismentioning
confidence: 99%
“…The results of parameter identification and uncertainty estimation are usually presented in the form of confidence intervals for model outputs and parameter marginal distributions. The problem was defined on the basis of Bayes estimation using the generalized likelihood uncertainty estimation (GLUE) approach (Beven and Binley, 1992;Romanowicz and Beven, 2006). Parameter distributions are obtained using the Bayes formula:…”
Section: Parameter Identification and Uncertainty Analysismentioning
confidence: 99%
“…For all three branches, water levels have visibly lowered for equal discharges due to riverbed subsidence, up to roughly 0.6 m within the entire study period. Following Berends et al (2019), who found that in the data there is no detectable effect of recent river interventions on water levels, we ignored river interventions. Also, due to time limitations we ignored hysteresis effects.…”
Section: Uncertainty Of Rating Curvesmentioning
confidence: 99%